ECOLOGICAL EDUCATION OF SOCIETY AS A NECESSARY COMPONENT FOR ENSURING BALANCED ECOLOGICAL AND ECONOMIC DEVELOPMENT (INNOVATIVE ECONOMY, 2020)
Boronos V.H., Pronikova Zh.S., Taraban N.V. ECOLOGICAL EDUCATION OF SOCIETY AS A NECESSARY COMPONENT FOR ENSURING BALANCED ECOLOGICAL AND ECONOMIC DEVELOPMENTPurpose. Improvement of the system of motivation to environmentally directed activity, analysis of advantages and possibilities of using methods of internal motivation: social, psychological, educational and training.Methodology of research. The theoretical and methodological basis of the research is the scientific works of scientists, the work of the scientific school on the economy of nature management O. Balatskyi. In the course of the research, methods of structural and logical analysis were used for determining the categories of internal and external motivation as well as for the classification of types of motivation; abstract-logical method – to identify the essence of the concept of "human ecological"; system analysis – in the study of problem issues of the system of domestic ecological education.The methods of structural and logical analysis are used in the course of the research for determining the categories of internal and external motivation as well as for the classification of types of motivation; abstract and logical method – to identify the essence of the concept of “human ecological”; system analysis – in the study of problem issues of the system of domestic ecological education.Findings. The concept of “ecological education” is defined, which means the continuous process of assimilation of values and concepts aimed at forming the abilities and attitudes necessary for understanding and estimating the interrelations between man and nature, and also foresees the development of the ability to take environmentally-directed solutions.The main disadvantages of applying external methods of motivation to environmentally oriented activities are analyzed. In the context of the financing gap, it is proposed to focus on internal motivations of social groups aimed at creating an “ecological person” and ecological thinking.Originality. Further methods of internal motivation have been developed, the role and significance of which are often underestimated by native scholars. The directions of the possible development of the domestic ecological education system are formed by updating their content, teaching technologies and teaching methods.Practical value. The results of the research are aimed at solving problems of reducing the negative destructive influence of man on the environment by changing the value system and constructing an ecological world outlook.Key words: motivation, environment, ecological education, ecological education, “ecological person”, ecological consciousness.
Keywords: Key words; motivation; environment; ecological education; “ecological person”; ecological consciousness.